2018
DOI: 10.2478/v10038-012-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

The mobility performance of the elderly before, during and after crossing over an obstacle

Abstract: Purpose. Tripping over objects is a major cause of fall-related injuries. The elderly feature decreased locomotor velocity with aging and delays in locomotion when encountering obstacles. Numerous studies have analyzed how the mobility performance of the elderly is affected when crossing over an obstacle. However, how is mobility performance affected when performing sequences of various locomotor movements (gait, changing direction, standing up and sitting down) that make up activities of daily living? To answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…This result was similar to previous studies (Zhang et al, 2011). Other studies also revealed that younger adults had a shorter stride time than older adults (Bovonsunthonchai et al, 2012;Uchiyama, Demura, & Sugiura, 2012) and that healthy people showed longer stride lengths and faster stride velocities than people with Parkinson's or cerebellar diseases (Kim et al, 2013;Vitório, Pieruccini-Faria, Stella, Gobbi, & Gobbi, 2010). McFadyen & Prince (2002) revealed that the longer stride time, shorter stride length and slower stride velocity in crossing obstacles may be positively related to a diminishing physical capacity in older adults.…”
Section: Discussionsupporting
confidence: 89%
“…This result was similar to previous studies (Zhang et al, 2011). Other studies also revealed that younger adults had a shorter stride time than older adults (Bovonsunthonchai et al, 2012;Uchiyama, Demura, & Sugiura, 2012) and that healthy people showed longer stride lengths and faster stride velocities than people with Parkinson's or cerebellar diseases (Kim et al, 2013;Vitório, Pieruccini-Faria, Stella, Gobbi, & Gobbi, 2010). McFadyen & Prince (2002) revealed that the longer stride time, shorter stride length and slower stride velocity in crossing obstacles may be positively related to a diminishing physical capacity in older adults.…”
Section: Discussionsupporting
confidence: 89%
“…When engaging with an obstacle, a greater adaptation strategy occurred, as exhibited with a considerable variation of the spatiotemporal gait and cOM variables in both with or without using a smartphone. When considering the age group that may be prone to injury from falls or trips, most attention is directed towards the elderly owing to the deteriorating body systems [34,35]. However, the challenging tasks of smartphone using together with locomotion performing in various environments could usually be observed in young lifestyles.…”
Section: Confronting Obstacle Challengementioning
confidence: 99%
“…The SCT course consisted of walking 3 m in a straight line, followed by a 2.355-m semicircular curve (radius, 0.75 m) and then a 3-m return straight path ( Figure 1). Colored tape (5 cm wide, approximately 0 cm thick) was used to demarcate the path [31].…”
Section: St and Sct Tasksmentioning
confidence: 99%